Density functional theory insights on the electronic and optical properties of zno in sunscreen applications - Zainuddin, Lili Widarti; Sheikh Abdul Aziz, Siti Sumaiyah; Azlisham, Hannan Aqilah; Faizam, Ilham Hibatullah; Ahmad Shukri, Intan Nurfilzah; Mohd Fahmy, Muhammad Faidz; Mohd Baharum, Nurjeeha Redwah; Juhaisham, Nur Naimi Afrina (2025)
The structural, electrical, and optical properties of zinc oxide (ZnO) was performed using density functional theory using CASTEP software with exchange correlation of generalized gradient approximation (GGA) with Perdew-Burke-Ernzerhof (PBE). The band gap energy of ZnO was observed at 3.27 eV after a Hubbard U correction at energy. Incorporating these corrections brought the band gap energy closer to experimental values. The absorption shows that ZnO fall in the UV region compliment with the band gap energy obtain.